Strategi Pengembangan Berkelanjutan Merk Couple Project Menggunakan Analisis SWOT dan Metode Business Model Canvas - Putri, Salma Sofyanti; Suryaningprang, Andre; Herlinawati, Erna; Sumawidjaya, Riyandi Nur (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2025)
Couple Project is a fashion brand that targets the young couple segment through its couple apparel products. Since its inception in 2022, the business has leveraged various digital platforms such as TikTok and Shopee as part of its marketing efforts. Nevertheless, it continues to face several challenges, including intense market competition, unstable sales performance, and suboptimal implementation of influencer marketing strategies. This research seeks to develop a sustainable growth strategy for Couple Project by employing an integrated analytical approach that combines SWOT analysis with the Business Model Canvas (BMC) framework. The study adopts a descriptive qualitative methodology, utilizing a combination of data collection techniques including in-depth interviews, direct field observations, and the distribution of structured questionnaires to both internal stakeholders and external partners associated with the company. The analysis reveals that the formulation of an effective development strategy should prioritize the optimization of digital platform utilization, the implementation of a more precisely targeted influencer marketing strategy, and the continuous improvement of product and service quality. These strategic directions are deemed essential for enhancing the brand's competitive positioning in the niche market of fashion products designed for young couples.